MAKEUP PRACTICES IN FASHION INNOVATIONS: SPECIFICS, FUNCTIONS - Шаркіна, А. (Art and Design, 2020)
The aim of the article is to identify the specifics and functional features of the artistic make-up in the design expressive means system at the level of joint techniques with make-up in theater and cinema. Methodology. The historical, analytical and comparative methods have been used in the study. The image-associative and stylistic analysis methods have been applied to the selected historical and modern examples of make-up practices. Summary. The specifics of theatrical make-up, make-up for cinema and fashion images have been examined on the examples of female images, common and distinctive features have been defined. The main functions of make-up have been exuded and realized by the author of the research in modern fashion images; the peculiarties of ratio of make-up with other components of the artistic image have been determined. The scientific novelty is in the actualization of the make-up problem in fashion-innovations within the scientific development, in determination of its specifics, which consists in the theater and cinema make-up artists’ basic techniques application and at the same time modern make-up, decorative, posthumous means usage. Practical significance. The relationship between traditional and innovative makeup practices in the fashion industry at the level f theoretical and methodological research and practical implementation of the makeup basic functions in the modern feale images creation have been revealed in the study. The results of the study focus on further research of the makeup types; the research results can be used in the practical activities of a make-up artist and in the teaching practice.